Analisis Kinerja Keuangan Perusahaan Sektor Pertambangan yang Terdaftar di BEI Tahun 2020-2023 - Istiani Istiani; Amri Amrulloh (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2025)
The financial performance of mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020-20203 period was greatly influenced by fluctuations in global commodity prices and macroeconomic conditions that had an impact on the company's competitiveness and profitability. Therefore, it is important to assess how companies in this sector are managing their financial performance amid various challenges and opportunities. This study analyzes financial performance using several main financial ratios, including liquidity ratios (Current Ratio and Quick Ratio), solvency ratios (Debt to Equity Ratio and Debt to Asset Ratio), profitability ratios (Return on Assets, Return on Equity, and Net Profit Margin), and activity ratios (Total Asset Turnover and Inventory Turnover). The method used to conduct the analysis is the quantitative descriptive analysis method, using data that has been taken based on the annual financial statements of companies listed on the IDX during the period. Sample selection using the purposive sampling method, resulted in 3 companies being analyzed. The results of the analysis of 81 data observed using the Multiple Linear Regression method showed that environmental performance and environmentally friendly products had a positive impact on the company's financial performance, while environmental poroscope and environmental activities did not show a significant influence on the company's financial performance.